2016
DOI: 10.1155/2016/8262561
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin and High Level Aminoglycoside Resistance inEnterococcusspp. in a Tertiary Health Care Centre: A Therapeutic Concern

Abstract: Aims. This study was aimed at knowing the prevalence of vancomycin and high level aminoglycoside resistance in enterococcal strains among clinical samples. Study Design. It was an investigational study. Place and Duration of Study. It was conducted on 100 Enterococcus isolates, in the Department of Microbiology, Pt. BDS PGIMS, Rohtak, over a period of six months from July to December 2014. Methodology. Clinical specimens including urine, pus, blood, semen, vaginal swab, and throat swab were processed and Enter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 18 publications
1
11
1
Order By: Relevance
“…In general, the prevalence of VRE is as low as as 4% in Europe and as high as 33% in North America. In India, the prevalence of VRE ranges from 0 to 30 % [7,8]. As a result, Enterococci have emerged as one of the leading therapeutic challenges when identified as a cause of serious; life threatening infections.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the prevalence of VRE is as low as as 4% in Europe and as high as 33% in North America. In India, the prevalence of VRE ranges from 0 to 30 % [7,8]. As a result, Enterococci have emerged as one of the leading therapeutic challenges when identified as a cause of serious; life threatening infections.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a high rate of resistance to fosfomycin was observed, while this antibiotic is as an alternative antibiotic against multidrug resistant organisms, including vancomycinresistant enterococcus (VRE) and extendedspectrum β-lactamase (ESBL) (47) which could be due to its excessive and inappropriate use. In addition, according to many reported studies (48)(49)(50), E. faecalis and E. faecium isolates exhibit high resistance to aminoglycosides including gentamycin and quinupristin/dalfopristin. Our findings showed that 21% of E. faecalis and 35% of E. faecium isolates are resistant to gentamycin while a high number of isolates were resistant to quinupristin/dalfopristin (81% and 79%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The isolates which show intermediate zone (7-9 mm) and resistance zone (<6 mm) to 120 µg disc were further tested for MIC by E-strip method. 7,8 MIC determination were done by using gentamicin Ezy MICTM (HiMedia) strip containing gradient concentration from 0.064 to 1024 mcg/ml. MIC >500 mcg/ml is considered as HLAR.…”
Section: Detection Of High-level Aminoglycoside Resistance (Hlar)mentioning
confidence: 99%